SOCIO-ECONOMIC LIFE AFTER THE DUTY OF CIVIL SERVANTS (A Descriptive Study of Retired Civil Servants of the Regional Government of Banda Aceh City) - MUHAMMAD TASAR S; Bahrein T Sugihen (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2017)
A person who is retired means experiencing a change in lifestyle from work to being unemployed. Human beings are not always able to do formal activities, especially for those who work in institutions or government agencies such as civil servants who move stopped, so the individual must try to adjust to changes that occur. When retirement comes there are things that will disappear namely, the loss of routine activities conducted since leaving until work home so someone will have much free time from the time before retirement. Therefore, this study aims to describe the socio-economic life full of civil servants (descriptive study of retired civil servants of the Regional Government of Banda Aceh city). The theory used is James Rational Choice theory S. Coleman. This study method using qualitative descriptive approach by conducting interviews, observation and literature study as data collection techniques. The results showed that after retirement many of the activities undertaken by civil servant pension that is doing economic action and social action, it is done to meet the needs of the family because the welfare of a pension is measured by the group they have, because the group determines the size of the salary of a person who obtained when they are retired. Someone who has retired will experience many problems whether it's health, social, economic and others. The activities performed by retired civil servants when they no longer work as civil servants, because retirees want to have a positive activity let alone done for economic and social needs are met. Assessed the body is still healthy, making these retirees perform various economic, affective and social measures in addition to supplement the family's income also to eliminate boredom. Activities undertaken make the pensioner feel happy through his old age, and not saturated spend his old days.Keywords: Social Economy, Retired, Civil Servants